2015
DOI: 10.1159/000369974
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and Genetic Characterization of Depression: Overlap with Other Psychiatric Disorders and Aging

Abstract: Genome-wide expression and genotyping technologies have uncovered the genetic bases of complex diseases at unprecedented rates. However, despite its heavy burden and high prevalence, the molecular characterization of major depressive disorder (MDD) has lagged behind. Transcriptome studies report multiple brain disturbances but are limited by small sample sizes. Genome-wide association studies (GWAS) report weak results but suggest an overlapping genetic risk with other neuropsychiatric disorders. We performed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
72
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(79 citation statements)
references
References 45 publications
7
72
0
Order By: Relevance
“…Consistent with what we observed for the effects of stress on Gabra2 expression in the PFC and NAc, subjects with MDD have increased Gabra2 expression in the cerebellum [86]. While single-nucleotide polymorphisms (SNPs) in the Gabbr2 gene are associated with MDD, human postmortem studies have not found altered expression of this gene in the brain (e.g., [85, 87]). Since we found increased expression of Gabbr2 in the PFC of XX mice but not XY mice, it is tempting to speculate that human postmortem studies might find an effect on Gabbr2 expression if analyses were stratified by sex.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Consistent with what we observed for the effects of stress on Gabra2 expression in the PFC and NAc, subjects with MDD have increased Gabra2 expression in the cerebellum [86]. While single-nucleotide polymorphisms (SNPs) in the Gabbr2 gene are associated with MDD, human postmortem studies have not found altered expression of this gene in the brain (e.g., [85, 87]). Since we found increased expression of Gabbr2 in the PFC of XX mice but not XY mice, it is tempting to speculate that human postmortem studies might find an effect on Gabbr2 expression if analyses were stratified by sex.…”
Section: Discussionsupporting
confidence: 71%
“…Our results for Gria1 are consistent with reports in the literature. For instance, GRIA1 expression is increased in BA9 [84, 87] and BA21 [85] in MDD subjects. We also saw increased Gria1 expression in the PFC and NAc of chronically stressed mice.…”
Section: Discussionmentioning
confidence: 99%
“…MDD also shows substantial heritability (approx. 0.37) [9, 10] and polygenic inheritance [11, 12]. However, promis ing genetic risk candidates for SCZ and MDD had not been well implicated until the emergence of recent large-scale genome-wide association studies (GWAS) [13-21].…”
Section: Introductionmentioning
confidence: 99%
“…This leads to the idea that BPD and MDD may have common genetic risk features. In fact, clinical, epidemiological, and genetic studies have revealed similar phenotypic characteristics between BPD and MDD [3, 6], and there are also overlapping risk genes, such as CACNA1C [7], CREB1 [8], and AS3MT [9-11]. It is thus proposed that genetic analyses of these two illnesses could uncover important genes underlying the symptoms observed in both dis­eases.…”
Section: Introductionmentioning
confidence: 99%
“…We then collected the published data of 15,318 cases and 91,990 controls worldwide and conducted a meta-analysis to further verify the replication results. In addition, considering the substantial genetic overlap between BPD and MDD [6, 29], we also examined rs1064395 in two MDD GWAS samples.…”
Section: Introductionmentioning
confidence: 99%